Ari Arranges Everything - Vernon, Katie (New York, NY : Running Press Kids, 2023)
Ari, a gender-fluid child, loves arranging things in neat orders, but realizes that not everything needs to have a perfect spot.
new kids book 2023 spring.
Ages 4-8.
Keywords: Perfectionism -- Fiction; Self-esteem; Picture books